2020
DOI: 10.1007/s12471-020-01474-2
|View full text |Cite
|
Sign up to set email alerts
|

Recommendations on how to provide cardiac rehabilitation services during the COVID-19 pandemic

Abstract: The ongoing coronavirus disease 2019 (COVID-19) crisis is having a large impact on acute and chronic cardiac care. Due to public health measures and the reorganisation of outpatient cardiac care, traditional centre-based cardiac rehabilitation is currently almost impossible. In addition, public health measures are having a potentially negative impact on lifestyle behaviour and general well-being. Therefore, the Working Group of Cardiovascular Prevention and Rehabilitation of the Dutch Society of Cardiology has… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
27
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(27 citation statements)
references
References 5 publications
0
27
0
Order By: Relevance
“…Furthermore, telerehabilitation can be offered relatively simply and affordably to a large, heterogeneous group using video or telephone consultations, text messaging and social media [ 18 ]. It has, therefore, been suggested that the availability of cardiac telerehabilitation should be upscaled during the current COVID-19 pandemic and that these (online) services also be made (freely) available to chronic CVD patients [ 18 , 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, telerehabilitation can be offered relatively simply and affordably to a large, heterogeneous group using video or telephone consultations, text messaging and social media [ 18 ]. It has, therefore, been suggested that the availability of cardiac telerehabilitation should be upscaled during the current COVID-19 pandemic and that these (online) services also be made (freely) available to chronic CVD patients [ 18 , 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…As of early 2020, delivery and introduction of many direct face-to-face health services have been stymied by the COVID-19 pandemic across the UK [9][10][11] and other afflicted nations [12][13][14][15] which has caused many providers to seek alternative modes of service delivery. This is an appropriate initial response as the risks from contracting COVID-19 to cancer populations are higher than in the general population, principally due to advanced age and the presence of comorbidities [16].…”
Section: Introductionmentioning
confidence: 99%
“…Currently, a system to provide phase 2 CR during the COVID-19 pandemic is under consideration [ 2 , 3 ]. The present study suggested that more careful intervention is needed with a focus on the decline of physical function, especially in patients aged 75 years and older.…”
Section: Discussionmentioning
confidence: 99%
“…Coronavirus disease 2019 (COVID-19) caused by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) may increase mortality in affected patients with cardiovascular disease (CVD) [ 1 ]. In addition, because it spreads from person to person via close contact, the delivery of cardiac rehabilitation (CR) is currently being hampered in many countries due to the COVID-19 pandemic [ 2 , 3 ].…”
Section: Introductionmentioning
confidence: 99%